A systematic review on outcome reporting in randomised controlled trials assessing treatment interventions in pregnant women with pregestational diabetes. (1st August 2021) - Kgosidialwa, O; Bogdanet, D; Egan, A; Newman, C; O'Shea, PM; Biesty, L; McDonagh, C; O'Shea, C; Devane, D; Dunne, F; ,
Abstract : Background: Pregestational diabetes mellitus (PGDM) is associated with adverse pregnancy outcomes. Studies assessing interventions to improve maternal and infant outcomes have increased exponentially over recent years. Several outcomes in this field of maternal diabetes are rare, making it difficult to synthesise evidence. Objectives: To collect outcomes reported in studies assessing treatment interventions in pregnant women with PGDM. Search strategy: CENTRAL, Web of Science, Medline, CINAHL, Embase and ClinicalTrials.gov from their inception until 27 January 2020. Selection criteria: Any randomised controlled trial assessing treatment interventions in pregnant women with PGDM reported in English. Data collection and analysis: Two independent reviewers assessed the suitability of articles and retrieved the data. Outcomes extracted from the literature were broadly categorised into maternal, fetal/infant or other outcomes by the study advisory group. Main results: Sixty‐seven of the 1475 studies identified fulfilled the inclusion criteria. The median number of outcomes reported per study was 15 (range 1–46). The majority of studies were from North America and Europe. Insulin and metformin were the most commonly investigated pharmacological interventions. Glucose monitoring was the most assessed technological intervention. In all, 131 unique outcomes were extracted: maternal ( n  = 69), fetal/infant ( n  = 61) and other ( n  = 1). Conclusions: Outcome reporting in treatment interventions trials of pregnant women with PGDM is varied, making it difficult to synthesise evidence, especially for rare outcomes. Systems are needed to standardise outcome reporting in future clinical trials and so facilitate evidence synthesis in this area of maternal diabetes. Registration: The systematic review was registered prospectively with the International Prospective Register of Systematic Reviews (PROSPERO) database (Registration number CRD42020173549). Tweetable abstract: Outcome reporting is heterogeneous in intervention trials of pregnant women with diabetes existing before pregnancy. Tweetable abstract: Outcome reporting is heterogeneous in intervention trials of pregnant women with diabetes existing before pregnancy.